2007
DOI: 10.1523/jneurosci.0399-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Radial Glia Generate Olfactory Bulb Interneurons in the Postnatal Murine Brain

Abstract: During embryogenesis, dorsal radial glia generate pyramidal cell neurons but not interneurons, and are thought to degenerate or transform into astrocytes in the postnatal brain. Ventral radial glia, in contrast, retract their processes to form GFAPϩ subventricular zone (SVZ) astrocytes that continue to generate interneurons into adulthood. We sought to fate map dorsal radial glia by codelivering an adenovirus expressing Cre recombinase and a lentivirus expressing dsRedExpress to the dorsal cortical surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
123
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(138 citation statements)
references
References 28 publications
12
123
0
3
Order By: Relevance
“…The former most likely corresponds to the structure that the authors of a previous study described as the ''subcallosal zone'' (19). Although it was initially described as a germinal zone that produces mainly oligodendrocytes, subsequent studies suggested that this dorsal area is also able to produce interneurons after birth (20,21). The migratory pathway directed from the SVZ to the nucleus accumbens we termed VMP, and the migratory cells in this pathway are probably identical to those described by De Marchis and colleagues (22).…”
Section: Discussionmentioning
confidence: 88%
“…The former most likely corresponds to the structure that the authors of a previous study described as the ''subcallosal zone'' (19). Although it was initially described as a germinal zone that produces mainly oligodendrocytes, subsequent studies suggested that this dorsal area is also able to produce interneurons after birth (20,21). The migratory pathway directed from the SVZ to the nucleus accumbens we termed VMP, and the migratory cells in this pathway are probably identical to those described by De Marchis and colleagues (22).…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have shown that neural stem cells in the adult brain are not a homogeneous population, but are regionally specified and normally produce only specific subtypes of olfactory bulb interneurons. These studies have proposed that different subpopulations of neural stem cells may be distinguished either by the expression of specific transcription factors 10,11,12,13,14 and/or by their regional localization along the dorsal-ventral and anterior-posterior extents of the lateral wall 9,15,16 . As more molecular markers of the regionally specified subpopulations of adult neural stem cells are identified, wholemount imaging should provide a comprehensive view of the parcelation of these different progenitor domains along the ventricular wall.…”
Section: Representative Resultsmentioning
confidence: 99%
“…An accurate analysis at different stages showed that radial glial cells convert their morphology by retracting their basal process (Merkle et al 2004). More recently, a similar analysis of lineage-tracing in vivo showed that also dorsal radial glia, labeled at P1 or P2, give rise to subependymal stem cells (Ventura and Goldman 2007).…”
Section: Adult Subependymal Stem Cellsmentioning
confidence: 91%